IDENTIFICATION OF AQUIFER TYPES AND POTENTIAL WELL LOCATIONS USING GIS AND REMOTE SENSING TECHNOLOGIES IN THE PISHIN LORA BASIN (Journal of Geography and Environmental Management, 2016)
GIS and Remote Sensing are powerful technologies for conducting research in remote and inaccessible regions in the world. Water is one of the basic necessities for the development of societies and agricultural communities. With the continuous rise in populations of the developing countries worldwide,many of these countries are now facing serious water shortages that require dedicated efforts to assess and develop their groundwater resources. One of these locations is the Pishin Lora basin inPakistan, an area that has been receiving waves of immigrants fleeing the war-infested neighboring Afghanistan. The watershed encompasses the Balochistan (Pakistan) and Kandahar Province (Afghanistan), two of the poorest and most dangerous areas in the World, where Taliban tribes live.Climate in the provinces is semi-arid, and extensive deserts cover most of the two regions. Increasing population, excessive use of groundwater, and arid climates (precipitation: ~ 100 mm/yr) have all contributed to progressive decline in groundwater levels (1989-present: 3m decline/yr). A cost-effective, interdisciplinary approach was adopted that integrates remote sensing data with observations extracted from other data sources (e.g., geochemistry, field geology, drilling, geophysics, and modeling) to:(1) assess the groundwater resources in these areas and to develop sustainable extraction scenarios, and (2) identify aquifer types, and select criteria for locating potential productive well locations. A manuscript titled “Remote Sensing Contributions to Hydrologic Modeling in Arid and Inaccessible Watersheds, Pishin Lora Basin, Pakistan" summarizing our results pertaining to Task 1 was recently published in the Journal of Hydrological Processes. In this manuscript, we outline our research andmethodology pertaining to the implementation of task 2. Specifically, the identification of isolated groundwater aquifers in fold and thrust belts using the Pishin Lora basin as our test site. The methodology was applied to the northeast part of Pishin Lora (NEPL) watershed, which is located on theborder of Pakistan and Afghanistan. Currently, the main water source for the local population in NEPL is from alluvial aquifers collecting runoff from surrounding mountains. Our findings indicate that additional potential isolated groundwater aquifers in bedrock should be targeted. These include: (1) nose of plunging folds (synclines), (2) fractured bedrock along faults and shear zones, (3) intersection of fractured bedrock (fault/fault; fault/shear zone; shear zone/shear zone), (4) intersection of shear zoneswith plunging folds. In general, areas where a number of folds, faults, fractures, or shear zones intersect are areas of high ground water potentiality. The intersection of these discontinuities will enhanceporosity and will create conditions favorable for ground water storage in fractured basement rocks.